Point of Sales System for Maizan Solution - NUR SYAFIQAH BINTI AYOP MAHATHIR; Nur Liyana binti Sulaiman (Applied Information Technology And Computer Science, 2026)
The current manual by Maizan Solutions in Bachok, Kelantan, has led to several operational inefficiencies, including poor inventory tracking, difficulty in identifying near-expiry products, and challenges in forecasting stock demands. To overcome this problem, three objectives have been established: to design a system based on the Object-Oriented Approach, to develop a web-based system, and to perform alpha and beta testing. Agile methodology was applied with eight sprints using the Laravel framework, Firebase and Artificial Intelligence, especially on the machine learning algorithm(linear regression) with the help of scanner. Eight use cases were applied with sequence diagram, activity diagram and class diagram to apply object oriented approach. The architecture pattern applied was Model-View-Controller (MVC). The results of functional testing (100%) and User Acceptance Testing (UAT) for Administrator in terms of functionality (94.98%), usability (96.65%), design (93.33%) and UAT for Cashier in terms of functionality (97.50%), usability (98.75%), design (98.75%). This project is significant to inventory management and transaction processing systems in the retail industry.